Altered Processing of Complex Visual Stimuli in Patients with Postconcussive Visual Motion Sensitivity - Allen, J.W.; Trofimova, A.; Ahluwalia, V.; Smith, J.L.; Abidi, S.A.; Peters, M.A.K.; Rajananda, S.; Hurtado, J.E.; Gore, R.K. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Vestibular symptoms are common after concussion. Vestibular Ocular Motor Screening identifies vestibular impairment, including postconcussive visual motion sensitivity, though the underlying functional brain alterations are not defined. We hypothesized that alterations in multisensory processing are responsible for postconcussive visual motion sensitivity, are detectable on fMRI, and correlate with symptom severity.MATERIALS AND METHODS: Twelve patients with subacute postconcussive visual motion sensitivity and 10 healthy control subjects underwent vestibular testing and a novel fMRI visual-vestibular paradigm including 30-second “neutral” or “provocative” videos. The presence of symptoms/intensity was rated immediately after each video. fMRI group-level analysis was performed for a “provocative-neutral” condition. Z-statistic images were nonparametrically thresholded using clusters determined by Z > 2.3 and a corrected cluster significance threshold of P = .05. Symptoms assessed on Vestibular Ocular Motor Screening were correlated with fMRI mean parameter estimates using Pearson correlation coefficients.RESULTS: Subjects with postconcussive visual motion sensitivity had significantly more Vestibular Ocular Motor Screening abnormalities and increased symptoms while viewing provocative videos. While robust mean activation in the primary and secondary visual areas, the parietal lobe, parietoinsular vestibular cortex, and cingulate gyrus was seen in both groups, selective increased activation was seen in subjects with postconcussive visual motion sensitivity in the primary vestibular/adjacent cortex and inferior frontal gyrus, which are putative multisensory visual-vestibular processing centers. Moderate-to-strong correlations were found between Vestibular Ocular Motor Screening scores and fMRI activation in the left frontal eye field, left middle temporal visual area, and right posterior hippocampus.CONCLUSIONS: Increased fMRI brain activation in visual-vestibular multisensory processing regions is selectively seen in patients with postconcussive visual motion sensitivity and is correlated with Vestibular Ocular Motor Screening symptom severity, suggesting that increased visual input weighting into the vestibular network may underlie postconcussive visual motion sensitivity.BESSBalance Error Scoring SystemDHIDizziness Handicap InventoryFEFfrontal eye fieldsMT/V5middle temporal visual areaPCSSPost Concussion Symptom ScalePCVMSpostconcussive visual motion sensitivityPIVCparietoinsular vestibular cortexVOMSVestibular Ocular Motor ScreeningVVASVisual Vertigo Analog Scale